(untitled) (Fiep Bulletin - online, 2011)
Sport in general and soccer in particular present themselves as transforming elements of society with a power of decisive influence in the development of citizens and professionals who work in the area most responsible for the positive aspects of this development. Futsal is presented as a means of social development at the time offers practitioners an opportunity to elements of the socialization and education that are essential in many everyday situations, besides the economic aspects generated as a result of futsal. Finally one can consider an indoor environment for social development, since it, is focused and is always directed to what is most important in sports that is the human person. As for the human being to education is essential and is the largest element of human development, educating through a sport that values the cooperation and integration of its participants is a highly satisfactory alternative and effective.